استراتيجية الترجمة الدلالية فى ترجمة كتاب "رسالة المعاونة والمظاهرة والمؤارزة" لمترجم محمد منوّر الزاهدى (دراسة تحليلية نقدية) - Mahmudah, Menik; Sari, Nanda Khafita; Somadani, Haikalus (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2022)
This study is aimed to describe the themes, semantical translation strategies with translator Muhammad Munawwir Az-Zahidy phrase that’s in the book of Risalatul Mu’awanah Wal Mudzoharoh Wal Muwazaroh. The method that is used in this research is descriptive qualitative method. The result of this study were (1) in the translator of the book of Risalatul Mu’awanah Wal Mudzoharoh Wal Muwazaroh, there are 125 phrase in translating with semantical translation strategies the themes were classified into 10 major themes, there are al-isti’ar (borrowing), al-‘adiil as-staqofy (cultural equivalent), al-‘adiil al-washfy (descriptive equivalent), al-muradif (synonym), terjemah resmi, at-takhfidh wa attausi’ (reduction and expantion), al-idhofah (addition), al-hadzf (delection), dan at-ta’diil (modulation). (2) Influence the strategy of semantical employed in translating the book Risalatul Mu’awanah Wal Mudzoharoh Wal Muwazaroh devided into 2, they are success and failure in translating teks.